Caring for an individual with mild cognitive impairment: a qualitative perspective of health-related quality of life from caregivers. (2nd September 2018) - Carlozzi, Noelle E.; Sherman, Carey W.; Angers, Kaley; Belanger, Mitchell P.; Austin, Amy M.; Ryan, Kelly A.
ABSTRACT: Objectives : Little is known regarding the effect that caring for an individual with Mild Cognitive Impairment (MCI) has on health-related quality of life (HRQOL). We sought to identify the most important aspects of HRQOL related to caring for an individual with MCI. Methods : Six focus groups were conducted with caregivers of individuals with MCI ( n = 32). Qualitative frequency analysis was used to analyze the data. Results : Findings indicated that caregivers most frequently discussed social health, including changes in social roles and an increased need for social support (51.2% of the total discussion). This was followed by mental health concerns (37.9%) centering on anger/frustration, and a need for patience in the caregiving role, as well as caregiver-specific anxiety. Other topics included physical health (10.0%; including the impact that stress and burden have on medical heath), and caregivers' cognitive health (0.9%; including memory problems in relation to caregiver strain, sleep disruption, and cognitive fatigue). Conclusions : Findings illustrate the multiple domains of HRQOL that are affected in individuals providing care for someone with MCI. Moreover, the findings highlight the need for extending support services to MCI caregivers, a group that is typically not offered support services due to the 'less severe' nature of an MCI diagnosis.